Evaluation of immunization coverage among children aged 12-23 months in Surendranagar city - Mahyavanshi, Darshan K.; Nagar, Shashwat S.; Patel, Mitali G.; Nagar, S. S.; Purani, Shyamal K.; Kartha, Girija P. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Infectious diseases are a major cause of morbidity & mortality in children. One of the most cost effective & easy methods for child survival is immunization. In May 1974, the World Health Organization (WHO) officially launched a global immunization programme known as Expanded Programme of immunization (EPI) to protect all the children of the world against 6 Vaccine Preventable Diseases by the year 2000. It was later redesignated as Universal Immunization Programme (UIP) since 1985. The objectives of this study were to assess the dropout rate and primary immunization coverage of children aged 12-23 months in Surendranagar city and to know the various reasons for partially or not immunizing the child. Methods: A community-based cross-sectional study. Thirty clusters were selected out of a total of 282 blocks of Surendranagar using the cluster sampling method. Cluster sampling method was used for sample selection and the proforma designed by UNICEF was used as a study tool. Sample size was 210 children (7 Children from each cluster) of aged 12-23 months. The obtained data were analyzed using appropriate statistical tests like Z test and X2 test. Results: Out Of the 210 surveyed children, 121(57.62%) were males and 89(42.38%) were females. Immunization card was available for 69.52% of children and fully immunized were 70.47%. Coverage was highest for BCG (95.71%) followed by OPV3 (82.85%), DPT3 (79.52%) and lowest for measles (75.23%). As far as the dropout rate is concerned, it was 21.39%, 10.21%, and 9.37% for BCG to measles, DPT1 to DPT3, and OPV1 to OPV3, respectively. Amongst the various reasons main reasons for dropout or unimmunization of children were ignorance in about 64% and lack of information regarding time, place and schedule (21%). Conclusions: Improvement should focus on reducing the dropout rate from DPT2/OPV2 to DPT3/OPV3 and improving coverage of measles and also Vitamin A.